Characteristics and Effects of Amnesty and Pardon - Mandozai, Mohammad Shafiq; Zadran, Amanullah (Integrated Journal for Research in Arts and Humanities, 2023)
Forgiveness is one of the most important concerns in criminal law, with the result that Forgiveness helps the community achieve stability, rehabilitation, and well-being by allowing the offender to be improved. Amnesty is granted under the law and is considered a cause of prosecution and dismissal of criminal proceedings. Pardon is only oversight of punishment and is subject to revocation, on the recommendation of the judiciary and with the approval of the head of state. In amnesty, prosecution and criminal proceedings are dropped, the sentence is suspended, and the effects of the conviction are removed. Pardon also removes the effects of a conviction. But it does not affect compensation and debt. Amnesty is applicable at all stages of a criminal case (detection, investigation, prosecution, and execution of a sentence), whereas a pardon is applicable only after the issuance of a final order and can’t be applied before.